2024
DOI: 10.1021/acs.energyfuels.3c05081
|View full text |Cite
|
Sign up to set email alerts
|

Geochemical Impact of High-Concentration Formate Solution Injection on Rock Wettability for Enhanced Oil Recovery and Geologic Carbon Storage

Oluwafemi P. Oyenowo,
Hao Wang,
Abouzar Mirzaei-Paiaman
et al.

Abstract: This paper presents new data on core-scale wettability alteration of carbonate porous media with FM concentrations up to 30 wt % in NaCl brine. Experimental data from Amott tests, core floods, calcite dissolution experiments, and zeta potential measurements were analyzed to mechanistically understand the wettability alteration observed in the experiments. Static calcite dissolution tests showed that the degree of dissolution increased with increasing FM concentration in NaCl brine, even with an initially neutr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 97 publications
0
2
0
Order By: Relevance
“…They pointed out that the presence of a wetting layer or a thicker wetting film on a tube would affect the wettability of channel and the distribution of water-oil two-phase flow. Oyenowo et al [16] experimentally studied the effect of aqueous formate solution on the core-scale wettability alteration of carbonate porous media and found that the fluid flowing in the porous media had an impact on the wettability of the cores. The initial oil-saturated core could reach a more water-saturated state by increasing the concentration of injected aqueous formate solution.…”
Section: Introductionmentioning
confidence: 99%
“…They pointed out that the presence of a wetting layer or a thicker wetting film on a tube would affect the wettability of channel and the distribution of water-oil two-phase flow. Oyenowo et al [16] experimentally studied the effect of aqueous formate solution on the core-scale wettability alteration of carbonate porous media and found that the fluid flowing in the porous media had an impact on the wettability of the cores. The initial oil-saturated core could reach a more water-saturated state by increasing the concentration of injected aqueous formate solution.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have worked with aqueous solutions based on formic acid [17] to enhance the CO2 solubility in brine or on formate ions [18,19] to enhance the pore-space utilization in carbon storage while avoiding various issues with CO2 storage. Additional benefits of the formate solution have been found for carbonate rocks concerning the wettability alteration to enhance oil recovery [18,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%